GRAIN YIEIL OF SORGHUM DEPENDING ON VAZIOUS OPTION FOR USING THE GROWTH STIMULATOR VEGESTIM IN THE NORTHEN STEPPE OF UKRAINE - Davydenko, S. Yu.; Rozhkov, A. O. (Scientific Progress & Innovations, 2022)
The aim of the research was to determine the influence of different variant of Vegestim gr owth stimulant application on grain yield of modern grain sorghum hybrids of different maturity groups. The research was conducted during 2019–2021 in the field of farm «Dunis» Kreminna district of Lugansk region. The two-factor experiment is based on the method of split-plot in three replications. The experiment studied four hybrids of grain sorghum of different maturity groups (plots of the first order): Iggor, Flagg, Yuki, Swat and six Vegestim growth stimulant applications (second-order plots): 1 – absolute control; 2 – the second control (treatment of seeds with water); 3 – treatment of seeds by Vegestim; 4 – seeds treatment and fertilization during 31–32 microphases; 5 – seed treatment and fertilization during 51–52 microphases; 6 – seed treatment + two leaf treatments in these phases. On average, according to the years and studied hybrids, the highest yield of sorghum grain (5.28 t/ha) was obtained in the variant of seed treatment and two foliar fertilization with Vegestim growth stimulator. High efficiency of Vegestim crop treatment at the beginning of tubing was noted. The grain yield of the early-ripening Yuki hybrid in this variant was the highest in the experiment – 4.53 t/ha. Carrying out two foliar treatments did not provide a significant increase in grain yield of this hybrid. Among the studied hybrids, the highest yield was formed by the middle-early hybrid of the French selection Flagg. On average, according to the years and variants of Vegestim growth stimulant application, the grain yield of this hybrid was 5.37 t/ha. The greatest changes in sorghum grain yield were affected by weather conditions of plant vegetation. The share of this factor was 54.0 %. Among the studied technological factors, features of hybrids had a greater influence on the variability of grain yield (contribution to variability – 28.2 %). The share of factor B in the variability of the indicator was 14.7 %. Among the studied early-maturing hybrids, a hybrid of domestic selection Swat had a significant advantage in terms of grain yield in all years, and among medium-early hybrids – a hybrid of French selection Flagg. Thus, these hybrids can be recommended to farms for cultivation, including in the technological plan the proposed option for the introduction of growth stimulant Vegestim, namely – pre-sowing seed treatment and two foliar fertilization – in the period 31-32 and 51-52 microphases according to the BBCH scale.